Influence of the loci of non-cavitated fissure caries on its detection with optical coherence tomography - Zain, E.; Zakian, Christian; Chew, Hooi Pin (Elsevier, 2018)
Objective: The main objective of this study was to evaluate the accuracy of optical coherence tomography (OCT) in detecting naturally occurring non-cavitated fissure caries (NCFC) in totality and at different loci by visually assessing cross-sectional OCT scans (B-scan) with an interpretation criterion. The secondary objective was to evaluate the agreement between dimensions of NCFC measured with OCT and polarized light microscopy (PLM). Methods: 71 investigation sites of sound fissure and naturally occurring NCFC on human extracted premolars were identified and scanned with a swept-source OCT. The teeth were then sectioned bucco-lingually at the investigation sites and imaged using PLM. Two calibrated examiners trained on the B-scan NCFC visual interpretation criteria established for this study, assessed the investigation sites and results were validated against PLM. Results: Detection sensitivity of B-scan for NCFC when fissures were assessed in totality, or on the slopes or walls separately are 0.98, 0.95, 0.94 and specificity are 0.95, 0.90, and 0.95. One-way ANOVA showed that width measurements of wall loci done with OCT and PLM were not statistically different. However, OCT height measurements of slope loci were statistically bigger with a constant bias of 0.08 mm (of which is not clinically significant) and OCT height measurements of wall loci were statistically smaller (0.57 mm) and Bland-Altman plots indicated presence of proportionate bias. Conclusion: Visual assessment of B-scans with the interpretation criteria resulted in both high specificity and sensitivity and were not affected by loci location. OCT width measurement of wall loci is in agreement with PLM. Clinical significance: Unanimous high sensitivity in this and previous studies indicate that visual assessment of B-scans reliably rule out NCFC. Detection accuracy was not affected by loci location. Width of wall loci and/or height of slope loci in OCT B-scan are to be used for monitoring NCFC but not height of wall loci.